2021
DOI: 10.1021/acs.jpca.1c02487
|View full text |Cite
|
Sign up to set email alerts
|

Quenching Mechanism of Uranyl(VI) by Chloride and Bromide in Aqueous and Non-Aqueous Solutions

Abstract: A major hindrance in utilizing uranyl­(VI) luminescence as a standard analytical tool, for example, in environmental monitoring or nuclear industries, is quenching by other ions such as halide ions, which are present in many relevant matrices of uranyl­(VI) speciation. Here, we demonstrate through a combination of time-resolved laser-induced fluorescence spectroscopy, transient absorption spectroscopy, and quantum chemistry that coordinating solvent molecules play a crucial role in U­(VI) halide luminescence q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…In KIT‐U‐1, the uranyl units are highly symmetric coordinated by the six oxygen atoms from the BTC linker in the equatorial plane [25b,27] . To our knowledge, the KIT‐U‐1 thin film presented here exhibited the largest ratio (>40 %) of the hot band to the main emission band at 503 nm (S 10 –S 01 ) among all uranyl‐based MOFs [6,28] …”
Section: Resultsmentioning
confidence: 83%
“…In KIT‐U‐1, the uranyl units are highly symmetric coordinated by the six oxygen atoms from the BTC linker in the equatorial plane [25b,27] . To our knowledge, the KIT‐U‐1 thin film presented here exhibited the largest ratio (>40 %) of the hot band to the main emission band at 503 nm (S 10 –S 01 ) among all uranyl‐based MOFs [6,28] …”
Section: Resultsmentioning
confidence: 83%
“…PARAFAC is a routine analysis used to deconvolute multidimensional emission spectra. 25,30–36 In the PARAFAC analysis, fitting the data with a two-species-model yielded for both ligands the best result.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of spectral patterns of either U(VI) or U(IV) shows that the PEC extracted U was pentavalent, consistent with the CV characterization. Although some previous studies on the homogeneous photoreduction of U(VI) showed that the photosensitization of aqueous U(VI) may lead to the formation of U(V) ( Tsushima et al., 2010 ; Haubitz et al., 2021 ; Li et al., 2019d ), upon illumination aqueous U(V) is very unstable and prone to re-oxidation if halide ions and/or dissolved oxygen are present in the reaction solution ( Haubitz et al., 2021 ; Tsushima et al., 2010 ). We examined the UV-vis absorption spectra of the reaction solution before and after illumination, and no characteristic peaks of U(V) were observed, suggesting no formation of stable U(V) via the homogeneous photosensitization pathway.…”
Section: Resultsmentioning
confidence: 99%